Evaluation of the effectiveness of wastewater treatment methods: maintaining the quality of water bodies in Indonesia - Kamarudin, Nur Salsabila (Universitas Nahdlatul Ulama Surabaya, 2024)
ollution in water bodies is an increasingly urgent problem and requires serious attention, this is due to poor waste management. In 2016, around 73.24% of 140 rivers from 34 provinces in Indonesia were in a polluted status. So that better management efforts and effective policies are needed to reduce river pollution. The use of water treatment technology consistently and sustainably is needed to overcome the challenges of water pollution and ensure that all levels of society have access to quality clean water, supporting public health and environmental sustainability.